Calculating the Mass of Subvisible Protein Particles with Improved Accuracy Using Microflow Imaging Data. Issue 2 (9th October 2014) - Kalonia, Cavan; Kumru, Ozan S.; Prajapati, Indira; Mathaes, Roman; Engert, Julia; Zhou, Shuxia; Middaugh, C. Russell; Volkin, David B.
<x xml:space="preserve">Abstract</x> Although formation of subvisible particles (1–100 μm) during manufacturing and/or storage is a major stability concern with protein therapeutics, particle numbers are often too low to permit for direct experimental measurement of their protein content (mass). The objective of this work was to develop a novel, accurate, and easy‐to‐implement method to calculate the mass of subvisible protein particles using particle number, size, and morphology data obtained from microflow imaging (MFI) measurements. The method was evaluated using (1) spherical and nonspherical polystyrene standards and (2) shake and stir‐stressed IgG1 mAb solutions. For extensively stressed mAb samples, in which protein mass loss after particle removal could be measured experimentally, calculated results were in good agreement and showed improvements in accuracy and precision compared with other methods. Improved estimates of protein mass in particles were made possible by using morphological data to better model particle volume, and by using literature‐based values for protein density and particle composition. This method improves estimations of protein particle mass when total amounts are too low to be measured experimentally and also facilitates a better understanding of protein particle formation by accounting for particle mass as well as number. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:536–547, 2015